Hubungan Kebiasaan Cuci Tangan Pakai Sabun (CTPS) pada Ibu dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Tanjung Buntung Kota Batam - Nadya Ulfa Kesumawardani; Made Tantra Wirakesuma; Fasida Dharma Yudastoro (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Diarrhea is a condition characterized by an increased frequency of bowel movements of more than 3 times within 24 hours accompanied by a change in the consistency of stools becoming softer or watery. Diarrhea is also the leading cause of death in Indonesia, accounting for 10.3% in 2020, with 2,131 cases reported in Batam city in 2023 and 3,713 cases in 2024. This study aims to determine the relationship between Handwashing with Soap Practices Among Mothers and the Incidence of Diarrhea in Toddlers. This research uses a quantitative approach with a Cross-Sectional design involving 67 respondents. The population of this study is all toddlers in the Working Area of the Tanjung Buntung Health Center in Batam City in 2024. This study employed a 'Cluster Random Sampling' technique, and the results showed that the handwashing with soap habits were poor, with 31 toddlers (46.3%) experiencing diarrhea, while respondents with good handwashing with soap habits did not experience diarrhea.